Relationship between cervical vertebral maturation and dental development in a sample of Yemeni children and adolescents. - Al-Aunhomi, Ali; Aldhorae, Khalid; Ishaq, Ramy; Al-Labani, Mohammed; Al-Maweri, Sadeq; Al-Ashtal, Amin (Universidad de Concepci?n, 2020)
Objective: This study was conducted to investigate the relationship between dental development and cervical vertebral maturation stages in a group of Yemeni children and adolescents. Materials and Methods: The study included digital panoramic radiographs and lateral skull cephalograms obtained from 207 Yemeni subjects122 females and 85 males aged between 8 to 18 years. Dental maturity was evaluated according to the method of Demirijian et al.,6 calcification stages of the left mandibular canines, first and second premolars and second molars were assessed. Skeletal maturity was assessed by the cervical vertebral maturation (CVM) stages according to the method of Baccetti et al.10 Correlation between CVM and dental maturation was evaluated by Spearman rank-order correlation coefficient (SROCC). Results: CVM and dental calcification stages were highly correlated (p<0.001) in both genders, ranging from 0.686 to 0.873 for females and 0.787 to 0.871 for males. Calcification stages of the second molars showed the strongest correlation with CVM. Conclusion: Calcification stages of the second molar may be used as a reliable maturation indicator. Dental maturation may be applied to determine the skeletal maturity status of Yemeni children and adolescents.